Information adoption of skincare and makeup product reviews on social media platforms in Vietnam - Pham, Dang Hong Ngoc (2017)
Modern consumers have been familiar with using online product reviews for their pre-purchase information gathering. In response, brands are increasingly taking advantage of this opportunity by using influential individuals such as bloggers to post favourable product reviews to promote their products. However, these word-of-mouth marketing strategies are not always welcomed by consumers, especially when they prefer unbiased, organic reviews to make informed choices. Thus, it is important to understand how consumers make decisions to adopt product reviews and what factors might affect this process. This dissertation aims to explore consumers’ information adoption when receiving skincare and makeup product reviews from beauty bloggers on social media platforms. The study examined 8 sites of 4 beauty bloggers in Vietnam as well as interviewed users and beauty bloggers to uncover how reviews are adopted. The dissertation proposes an integrative model of information adoption on social media platforms and identifies complex interconnections between the factors. Moreover, this study takes into account new social media platforms and compares their effects on information adoption. The findings extend extant knowledge of information adoption and suggest the factors that marketers should pay attention to when designing an influential product review.